Targeting a global health problem: Vaccine design and challenges for the control of tick-borne diseases - de la Fuente, José; Contreras, Marinela; Estrada-Peña, Agustín; Cabezas-Cruz, Alejandro (Vaccine, 2017)
It has been over twenty years since the first vaccines for the control of tick infestations became commercially available. These vaccines proved their efficacy and the potential of this approach for the control of tick-borne diseases (TBDs), which represent a growing burden for human and animal health worldwide. In all these years, research in this area has produced new tick-derived and pathogen-derived candidate protective antigens. However, the potential of vaccines for the control of TBDs has been underestimated due to major challenges to reduce tick infestations, pathogen infection, multiplication and transmission, tick attachment and feeding time and/or host pathogen infection. Nevertheless, vaccines constitute the most safe and effective intervention for the control of TBDs in humans, domestic and wild animals.
Keywords: vakcíny; Tick-Borne Diseases; Tick-borne diseases; Immunology; Ticks; Animals; Global Health; Humans; celosvětové zdraví; Risk; Tick; Vaccine; lidé; klíšťata; zvířata; Vaccines; Omics; nemoci přenášené klíšťaty